Domoic Acid-Induced Neurotoxicity Is Mainly Mediated by the AMPA/KA Receptor: Comparison between Immature and Mature Primary Cultures of Neurons and Glial Cells from Rat Cerebellum - Helena T. Hogberg; Anna K. Bal-Price (Journal of Toxicology)
Domoic acid (DomA) is a naturally occurring shellfish toxin that can induce brain damage in mammalians. Neonates have shown increased sensitivity to DomA-induced toxicity, and prenatal exposure has been associated with e.g. decreased brain GABA levels, and increased glutamate levels. Here, we evaluated DomA-induced toxicity in immature and mature primary cultures of neurons and glial cells from rat cerebellum by measuring the mRNA levels of selected genes. Moreover, we assessed if the induced toxicity was mediated by the activation of the AMPA/KA and/or the NMDA receptor. The expression of all studied neuronal markers was affected after DomA exposure in both immature and mature cultures. However, the mature cultures seemed to be more sensitive to the treatment, as the effects were observed at lower concentrations and at earlier time points than for the immature cultures. The DomA effects were completely prevented by the antagonist of the AMPA/KA receptor (NBQX), while the antagonist of the NMDA receptor (APV) partly blocked the DomA-induced effects. Interestingly, the DomA-induced effect was also partly prevented by the neurotransmitter GABA. DomA exposure also affected the mRNA levels of the astrocytic markers in mature cultures. These DomA-induced effects were reduced by the addition of NBQX, APV, and GABA.